Manejo de viveros de tolerancia a la sequia en el frijol : perspectiva fisiologica - White, Jeffrey W. (International Center for Tropical Agriculture, 1985)
The slow progress made in the search for var. with higher levels of drought tolerance is partially due to the inefficient management of nurseries. At CIAT, screening for tolerance has evolved at almost all stages, from planning through the analysis of final results. This report describes several decisions that have been taken to increase the efficiency of nurseries. Compared with random block designs, the use of lattice designs has increased efficiency by over 50 percent. The choice of planting dates on the basis of possible stress periods allows greater precision in the selection of stress periods. The use of multiple planting dates is also promising. For preliminary evaluations, the use of multiple regimes does not seem necessary. The analysis of results of a trial on moisture gradients (line source) suggest that the technique is not as reliable as on-site evaluations and multiple planting dates. Although these techniques are considered promising to evaluate drought tolerance, they also require well-managed nurseries. (AS- CIAT)